OsJAZ9 acts as a transcriptional regulator in jasmonate signaling and modulates salt stress tolerance in rice. (March 2015) - Wu, Hua; Ye, Haiyan; Yao, Ruifeng; Zhang, Tao; Xiong, Lizhong
Highlights: Suppression of OsJAZ9 resulted in reduced salt tolerance which was mainly due to the changes in K + homeostasis. OsJAZ9 interacts with several bHLH transcription factors including OsbHLH062. Both OsJAZ9 and OsNINJA repressed OsbHLH062-mediated transcription activation. Abstract: The basic functions of plant-specific TIFY proteins as transcriptional regulators have been reported in plants. Some TIFY genes are responsive to abiotic stresses, but the functions of these genes in stress tolerance have seldom been reported. OsJAZ9 is a member of the JAZ subfamily which belongs to the TIFY gene family in rice ( Oryza sativa ). Suppression of OsJAZ9 resulted in reduced salt tolerance. The altered salt tolerance was mainly due to changes in ion (especially K + ) homeostasis, which was supported by the altered expression levels of several ion transporter genes. The OsJAZ9 -suppression rice plants showed increased sensitivity to jasmonic acid (JA) treatment. OsJAZ9 interacts with OsCOI1a, a component of the SCF COI1 E3 ubiquitin ligase complex, in a coronatine-dependent manner, suggesting that OsJAZ9 is involved in the regulation of JA signaling. OsJAZ9 interacts with several bHLH transcription factors including OsbHLH062 via the Jas domain. OsbHLH062 can bind to an E-box in the promoters of the ion transporter genes such as OsHAK21, and most of these ion transporter genes are responsive to JA treatment. We found that OsJAZ9 can also interact with OsNINJA, a rice homolog of the Arabidopsis thaliana transcriptional repressor NINJA in JA signaling. Both OsJAZ9 and OsNINJA (Novel Interactor of JAZ) repressed OsbHLH062-mediated transcription activation. These results together suggest that OsJAZ9 acts as a transcriptional regulator by forming a transcriptional regulation complex with OsNINJA and OsbHLH to fine tune the expression of JA-responsive genes involved in salt stress tolerance in rice.